2011
DOI: 10.1155/2011/126562
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Oral Bioavailability of Puerarin by Polybutylcyanoacrylate Nanoparticles

Abstract: The interest using novel drug delivery systems to improve oral bioavailability of drug with poor solubility is increasing. In this study, a new oral delivery system, polybutylcyanoacrylate nanoparticles (PBCNs), was introduced to improve the oral bioavailability of puerarin (PUE). PUE-loaded PBCN was successfully prepared by anionic polymerization method. Characterization of PUE-loaded PBCN was evaluated with morphology, size, zeta potential, and in vitro release study. The PBCN loading PUE exhibited a spheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…It might have further been incorporated in polymer NPs by emulsion during the polymerization. 18 This rapid polymerization reaction occurred gradually when the pH was adjusted stepwise (pH .5.0).…”
Section: Results and Discussion Preparation And Physicochemical Charamentioning
confidence: 99%
See 3 more Smart Citations
“…It might have further been incorporated in polymer NPs by emulsion during the polymerization. 18 This rapid polymerization reaction occurred gradually when the pH was adjusted stepwise (pH .5.0).…”
Section: Results and Discussion Preparation And Physicochemical Charamentioning
confidence: 99%
“…In the present study, the difference in pharmacokinetics results and the in vitro release profile of QT-PBCA NPs may be caused by the possible enterohepatic recirculation. 18 The result indicated that the relative bioavailability of QT-PBCA NPs and QT-PBCA+P-80 enhanced the QT bioavailability by 2.38-and 4.93-fold respectively as compared to that of free QT. The increased bioavailability of PBCA NPs may be a co-work of direct uptake of NPs through the GI tract.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…They both have potent antioxidant activity, which allows them to scavenge free radicals, they are widely used for the treatment of cardiocerebrovascular diseases [13][14][15] , they are readily metabolized by certain enzymes, and they can undergo methylation, glucuronidation and sulfation in vivo [16,17] . Although both (+)-C and Pue showed poor oral bioavailability when individually administered at a single dose [18,19] , co-administration of both drugs achieved enhanced therapeutic effects. Songlingxuemaikang Capsule ® , which is a type of traditional Chinese medicine (TCM) compound preparation that is utilized for the treatment of some cardiocerebrovascular diseases and hypertension in clinical applications [20] , mainly contains Pinus massoniana Lamb needle and Pueraria lobata (Willd) Ohwi root extracts, the bioactive substances of which are (+)-C and Pue [21,22] .…”
Section: Introductionmentioning
confidence: 99%